Los trabajos y las artes (I). Estado de la cuestión - Proyecto - Koldobsky, Daniela (2015)
Works and arts (I). State of play Work has been expelled from art as the artist was defined as an ex-nihilo creator, definition that underlines attributes such as inspiration and genius that deny all possibility of learning, skill or practice and are sustained under a certain innate conception that doesn’t seem to require explanation. However, modern and contemporary art in its diverse disciplines and languages have again and again proventhe diversity and extension of the production means and operations that often question all specificity of the artistic work, as they incorporate knowledge, technologies and production processes that belong to other practices and social life scopes, while at the same time works at the circulation, exhibition and artistic reception have amplified and became complex. This investigation project proposes, on one hand, to examine the station occupied by the notion of work in a portion of current art theory (and thus to constitute a state of play), and on the other hand, to start digging into the knowledge, techniques and ways present in various zones of contemporary argentine art in both production and reception.